حلية الفائدة القرضية في المصارف الحكومية دراسة في التكييف الفقهي - م.د. محمد جبار هاشم الجبوري ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
There is no doubt that money and banks occupy great importance to the work of the modern economy and its development, to the role that money and banks play in the economic life as contain in the trading, exchanges and deals on a large scale. These deals are made using money either on a locally or on internationally. The strong and close relationship links between money and the banks can not be separated, the money of great importance in the work of banks and banks, in turn, play an important role by generating money and dealing in the areas of lending, borrowing and investment. The fact that the economic Islamic system is considered as one of free systems, and that because of its reliance on the individual in all its systems and aspects of his life, but that is not an individual system handling person problems with his own interests, rather it considers the natural rights of the individual and his/her benefits and personal interests as posts social solidarity with the social interests of the group as a whole. The individual is the basis of the system and the state, so Islam came to resist all that bad aspects in humans, such as greed, exploitation and monopoly and also came to urge people to each other Steering what is good for them and cooperation between the people in the framework of morals. Islam has introduced an economic system that is based on an independent basis of its characteristics that distinguish them from the rest of the other economic systems, as the Islamic system, an extract of the Quran and the pure Sunnah, and then of the doctrinal heritage. The Islamic system is based on a special conception of money and property right, it can be confined to several rules including, but not limited to: that Almighty Allah is the owner of everything and that man is trustworthy in this property and that money is not a commodity but a means to reach certain goals and that the ownership of this money is only a tool to get to those ends. Money should be obtained by lawful and is also used by lawful and that man is the first responsible of it, by restricting the ways of earning and use through the prohibition of onshore, compactness and extravagant, which means that its unpermitted to humans may assemble wealth and not squandered and use money on an ongoing basis in order to always make it productive. As a result of what mentioned above, the focus of the first part of this research comes on the study of the ownership of state and bank to find out what results that ownership of the provisions in terms of money source and ownership and the consequences of those provisions as rules, "an anonymous owner," and others. The second part in this research deals with the study of idiosyncratic adaptation for the bank benefit to manifest through legitimate earnings for money concepts by the anyone who employs his/her money in state banks or when does he/she to borrow money from these banks to be used that money as a means to reach his/her goals, and this is the main axis that the problem of this research is about, which research seeks to solve by finding possible legitimate( legal ) means and methods that allow the Muslim people to deal with those means which protect Muslims from falling into the illegal contraband. Find a conclusion dealing with the results that came out then followed by a list of sources and references adopted and then by a summary in English that end.